2017
DOI: 10.1103/physreva.95.063613
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional dipolar gap solitons in free space with spin-orbit coupling

Abstract: We present gap solitons (GSs) that can be created in free nearly two-dimensional (2D) space in dipolar spinor Bose-Einstein condensates with the spin-orbit coupling (SOC), subject to tight confinement, with size a ⊥ , in the third direction. For quasi-2D patterns, with lateral sizes l ≫ a ⊥ , the kinetic-energy terms in the respective spinor Gross-Pitaevskii equations may be neglected in comparison with SOC. This gives rise to a bandgap in the system's spectrum, in the presence of the Zeeman splitting between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 92 publications
1
60
0
Order By: Relevance
“…If the SOC is too strong, figure 6 in [51] suggests that the LHY correction may qualitatively change its form. In fact, the mean-field part of the model may also undergo a dramatic change in the case of strong SOC, replacing the regular solitons by gap solitons, as shown in [22]. Thus, both the mean-field and LHYparts of the model adopted in the present work are relevant (the LHY part is displayed below), provided that the SOC does not grow too strong.…”
Section: Mms Under the Action Of The Lhy Termsmentioning
confidence: 83%
See 1 more Smart Citation
“…If the SOC is too strong, figure 6 in [51] suggests that the LHY correction may qualitatively change its form. In fact, the mean-field part of the model may also undergo a dramatic change in the case of strong SOC, replacing the regular solitons by gap solitons, as shown in [22]. Thus, both the mean-field and LHYparts of the model adopted in the present work are relevant (the LHY part is displayed below), provided that the SOC does not grow too strong.…”
Section: Mms Under the Action Of The Lhy Termsmentioning
confidence: 83%
“…Recently, we have found that SOC can also support stable 2D gap solitons in the free-space spinor BEC with dipole-dipole interactions (possibly combined with contact interactions, which cannot create such solitons by themselves) in the presence of the Zeeman splitting between the components [22]. In that case, the bandgap in the systemʼs spectrum, which is populated by the gap solitons, is a result of the interplay of the SOC and Zeeman splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[57], while families of gap solitons obtained in the model with the dipole-dipole interaction, considered in Ref. [30], extend into the bands (however, gaps were never empty in that system). Fig.…”
Section: A Fundamental Solitonsmentioning
confidence: 90%
“…Similar settings can be implemented in optics, predicting the creation of spatiotemporal solitons ("light bullets") in planar dual-core waveguides and twisted cylinder waveguide with the self-focusing Kerr nonlinearity, respectively [39][40][41]. Further, the interplay between the SO coupling and anisotropic dipole-dipole interactions in 2D free space can create stripe solitons [42], solitary vortices [43][44][45][46], and gap solitons [47] (2D free-space gap solitons can also be created in SO-coupled BECs with contact interactions, at appropriate values of parameters [48]). Recently, it was also found that the combination of LHY and SO-coupling terms in 2D creates anisotropic "quantum droplets" in spinor BECs [12].…”
Section: Introductionmentioning
confidence: 95%